The impact of a fixed mindset on life satisfaction and academic anxiety - Sanjita, Sanjita; Sharma, Nidhi (Journal of Neonatal Surgery, 2025)
This study explores how a fixed mindset affects individuals' life satisfaction and academic anxiety. Based on Carol Dweck’s psychological theory, the fixed mindset is defined by the belief that intelligence and abilities are inherent and unchangeable. The research examines the influence of this mindset on personal development, emotional health, and academic success, emphasising behaviours like avoiding challenges, being sensitive to criticism, and fearing risks. It also compares the outcomes of a fixed mindset with those of a growth mindset, underscoring the educational and professional advancement implications. This study explores the fixed mindset—the belief that one's abilities and intelligence are static—and its impact on personal growth, mental health, and risk-taking. The research involved 100 emerging adults aged 18 to 25 who completed self-report measures to assess their mental orientation and related behaviours. The findings from correlational and regression analyses indicate that a fixed mindset is associated with avoiding challenges, heightened sensitivity to criticism, and prioritizing validation over personal growth. These traits contribute to increased psychological distress and hinder personal development. The discussion is framed within mindset theory, highlighting the contrast between growth and fixed mindsets. The study underscores the importance of nurturing a growth mindset for self-improvement.